Profile of hyponatremia in a tertiary care centre in North India - Mittal, Mahim; Deepshikha, .; Khurana, Hunny (International Journal of Advances in Medicine, 2016)
Background: Hyponatremia is the commonest electrolyte imbalance. Hyponatremia is a heterogenous disorder and classified into hypovolemic, euvolemic and hypervolemic types depending on the volume status of the patient. Approach is based on etiology and type of hyponatremia. The aim of the present study was to determine the profile of hyponatremia in adult patients including underlying etiology, type, clinical features and outcome Methods: The study was conducted at BRD medical college Gorakhpur, India between July 2014 to August 2015 after approval by the ethical committee. Consenting patients >18 years of age with hyponatremia (<130meq/l) were included and investigated as per protocol. Based on volume status and urinary sodium patients were classified as euvolemic, hypervolemic and hypovolemic. Results: N = 250, mean age 53.9 years. 56% males, 154(61.6%) patients had euvolemic, 53 (21.2%) hypervolemic and 43(17.2%) hypovolemic hyponatremia. The most common causes for euvolemic, hypervolemic, hypovolemic hyponatremia were CNS infections, CLD and acute gastroenteritis respectively. Neurologic symptoms were more common in severe as compared to mild hyponatremia (69.7% versus 8.1%). Seizures attributable to hyponatremia were seen in 44 patients (17.6%), all with severe hyponatremia. Overall mortality was 14%. Deaths were more frequently seen in patients with severe hyponatremia as compared to patients with mild hyponatremia (25.5% vs. 4.7% P = 0.035). Conclusions: Euvolemic hyponatremia is the most common type seen in hospitalized patients and is associated mainly with intracranial pathologies. Severe hyponatremia is significantly associated with neurological manifestations and higher mortality.